Inclusive Philanthropy and Poverty Alleviation in Indonesia: A Study of the Philosophy of Deliberative Justice - Masykur, Masykur; Kurniawan, Ade Fakih; Sumintak, Sumintak; M. Nanda, Fauzan; Suryani, Ade Jaya (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
This study explores the role of inclusive philanthropy in addressing the persistent challenge of poverty in Indonesia’s multicultural society, where structural disparities are often shaped by religious, ethnic, and socio-economic differences. While philanthropic traditions such as zakat, infaq, sadaqah, and waqf have long been central to Islamic social practice, their implementation has often remained confined within exclusive communal or religious boundaries, limiting their transformative potential. Taking the case of the LAZ Griya Yatim & Dhuafa Foundation in Cilegon City, this research seeks to understand how philanthropic initiatives that transcend identity-based limitations can contribute to more equitable and sustainable welfare distribution. Employing a qualitative approach that includes in-depth interviews with key philanthropic stakeholders and critical literature analysis, the study draws on Jürgen Habermas’s theory of deliberative justice to examine how inclusive philanthropy can operate within the public sphere as an instrument of both solidarity and justice. The analysis reveals that dialogically grounded and participatory philanthropy, when responsive to the pluralism of its social context, has the capacity to strengthen civil society engagement and promote fair access to welfare resources. It was found that inclusive philanthropy is an effective strategy for alleviating poverty regardless of ethnicity, religion, or race. These findings emphasize deliberative justice to ensure a fair welfare distribution through the active participation of civil society. It is hoped that inclusive philanthropic practices will increase through government policies in more structured state philanthropy and active involvement in the public sphere. Ultimately, this study offers both theoretical insight and practical direction for how inclusive philanthropic models can be integrated into broader strategies of poverty alleviation and social transformation in plural societies.